Community Service for Improving Health Services and Early Detection of Hypertension Complications in the Elderly in Bulak Village, Surabaya - Museyaroh; Juliana Juliana Christyaningsih (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
ABSTRACT Bulak Village in Surabaya has a population of approximately 22,330 people, with a relatively high proportion of elderly residents. The elderly are a vulnerable group for hypertension and anemia. According to the 2023 Indonesian Health Survey, the national prevalence of hypertension reached 30.8%, and East Java is one of the provinces with the highest rate (36%). To address this issue, a team of lecturers and staff from the Surabaya Ministry of Health Polytechnic conducted community service at the elderly health post in the Bulak urban village area of Surabaya. Activities include socialization, education, and blood pressure, hemoglobin, and hematocrit checks, targeting 49 elderly individuals. The results show that 36.7% of the elderly have stage 1 hypertension and 8.2% have stage 2 hypertension. A total of 51% of respondents have anemia (low Hb), and 67.3% have below-normal hematocrit levels. This condition reflects weak early detection and a lack of awareness regarding the importance of routine health checkups for the elderly. Factors contributing to low knowledge among the elderly include limited examination tools and costs, as well as the suboptimal role of community health posts in disease prevention and control. Therefore, continuous education, strengthening elderly health posts, and the involvement of families and communities are needed to support healthy lifestyles and regular treatment for the elderly. INDEX TERMS elderly, hypertension, hemoglobin, hematocrit.